International Marketing / Sixth Edition - Sarathy Ravi; Terpstra Vern (The Dryden Press, 1994)
The International Environment, The Concept of Global Marketing, Economic Environment: The World Economy, Economic Environment: The Foreign Economies, Cultural Environment: The People of the World, The Political-Legal Environment, International Marketing Management, Global Marketing Strategy, International Product Policy: The Basic Product and Its Attributes, Distribution: Entering Foreign Markets, International Promotion: Advertising, International Marketing of Services, Coordinating International Marketing, The Future of International Marketing.
The International Environment, The Concept of Global Marketing, Economic Environment: The World Economy, Economic Environment: The Foreign Economies, Cultural Environment: The People of the World, The Political-Legal Environment, International Marketing Management, Global Marketing Strategy, International Product Policy: The Basic Product and Its Attributes, Distribution: Entering Foreign Markets, International Promotion: Advertising, International Marketing of Services, Coordinating International Marketing, The Future of International Marketing.